2010
DOI: 10.1134/s107042801005012x
|View full text |Cite
|
Sign up to set email alerts
|

New orthogonally functionalized synthetic blocks from R-(−)-carvone

Abstract: The intramolecular cyclization of (-)-cis-carveol under iodine treatment afforded (1R,5R,6S)-6-iodomethyl-2,6-dimethyl-7-oxabicyclo[3.2.1]oct-2-ene that was subjected to allyl oxydation with the complex CrO 3 DMP giving a synthetically valuable building block, (1R,5R,6S)-6-iodomethyl-2,6-dimethyl-7-oxabicyclo[3.2.1]oct-2-ene-4-one. In the latter the double bond was cleaved by ozonization to obtain the expected trioxo derivative, and the subsequent ozonolysis of its enol form provided a multiple functionalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This compound was obtained by means of the procedure described in the literature and its spectroscopic data were identical to those described in the literature. 34 Preparation of 6a. This compound was obtained by means of the procedure described in the literature and its spectroscopic data were identical to those described in the literature.…”
Section: Synthesis Of the Substratesmentioning
confidence: 99%
“…This compound was obtained by means of the procedure described in the literature and its spectroscopic data were identical to those described in the literature. 34 Preparation of 6a. This compound was obtained by means of the procedure described in the literature and its spectroscopic data were identical to those described in the literature.…”
Section: Synthesis Of the Substratesmentioning
confidence: 99%
“…This compound was prepared following a procedure reported in the literature. NMR data were identical to those described in the literature …”
Section: Synthetic Proceduresmentioning
confidence: 68%
“…it has been demonstrated that the use of hydrotalcites made possible to obtain in good yield from a commercially available material in both enantiomeric pure forms chiral compounds such as lactones 7 and 8 that can be used in organic synthesis as valuable synthons (Valeev et al 2010).…”
Section: Discussionmentioning
confidence: 99%